The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.28933/ijoar-2019-03-0705
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cognitive Training Program for Cognitively Impaired Older Adults: A Pilot Randomized Control Trial

Abstract: This pilot investigation evaluated the effectiveness of a cognitive training program for older adults with cognitive impairment. Methods: A sample of 23 individuals were randomly assigned to either a 24-session cognitive training program or a wait-list control group. Cognitive training sessions required participants to complete activities that targeted the following cognitive domains: attention, visual and verbal memory, visual spatial skills, processing speed, executive functioning, and language. A battery of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…Evidences showing that cognitive training improve behavioral performance in normal aging and mild cognitive impairment have strengthened the first hypothesis and indicated its possible use to prevent or reduce cognitive decline (Vermeij et al, 2016). Buchanan et al (2019) conducted a systematic review about cognitive training and reported small to large effects for cognitive improvements in different domains, such as general cognitive functioning, attention and memory, visual recognition, perceptual speed and for some executive functions. Hill et al (2016) also conducted a systematic review and meta-analysis study specifically to investigate the effects of computerized cognitive training in elderly and found small to moderate impact on global cognition, attention, working memory, learning, and memory.…”
Section: Discussionmentioning
confidence: 99%
“…Evidences showing that cognitive training improve behavioral performance in normal aging and mild cognitive impairment have strengthened the first hypothesis and indicated its possible use to prevent or reduce cognitive decline (Vermeij et al, 2016). Buchanan et al (2019) conducted a systematic review about cognitive training and reported small to large effects for cognitive improvements in different domains, such as general cognitive functioning, attention and memory, visual recognition, perceptual speed and for some executive functions. Hill et al (2016) also conducted a systematic review and meta-analysis study specifically to investigate the effects of computerized cognitive training in elderly and found small to moderate impact on global cognition, attention, working memory, learning, and memory.…”
Section: Discussionmentioning
confidence: 99%
“…Estudos apontam que o treino cognitivo surte efeito positivo não apenas para idosos saudáveis, como também para aqueles com comprometimento cognitivo leve (CCL) (Buchanan, 2019;Reijnders et al, 2012;Simon et al, 2012). Além disso, alguns estudos com neuroimagem sugerem que o treino também exerce impacto direto sobre o cérebro (Duda & Sweet, 2020).…”
unclassified